Pengelolaan Kelas Dalam Meningkatkan Hasil Belajar di RA Al-Fazri - Ahyar Ahyar; Karsela Karsela; Nuri Anggriyani; Nurmaya Rafika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In teaching and learning activities there are two things that also determine the success or failure of a teaching and learning process, namely classroom management and teaching itself. The two things are interdependent. Students can learn well, in a natural atmosphere without pressure and in conditions that stimulate learning. To create an atmosphere that fosters a passion for learning, increases student achievement, and makes it more possible for teachers to provide guidance to students in learning, adequate classroom management is needed. So from that, researchers are interested in taking the title of research on classroom management in improving learning outcomes at RA AL-FAZRI Keywords: learning activities, teaching, classroom management